Impact of climate change on Africa’s major lakes: a systematic review incorporating pathways of enhancing climate resilience - Mutanda, Gideon W.; Nhamo, Godwell (Frontiers in Water, 2024)
Climate change is a global phenomenon with profound effects on ecosystems, including lakes, which are an important source of fresh water, fisheries, and biodiversity conservation. Africa, with its limited freshwater resources, remains vulnerable to climate change impacts. This study systematically reviews the literature to understand the impact of climate change on four major African lakes (Chad, Victoria, Tanganyika, and Malawi/Nyasa/Niassa) and to identify pathways for enhancing their resilience and society’s dependent on them. The review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA) 2020 guideline using journal articles extracted from the Scopus and Google Scholar databases and analysed using ATLAS.ti 24 software. The study found that climate change and extreme climate events (ECEs) are disproportionately affecting the physical, chemical, and biological characteristics of the lakes, leading to changes in lake levels, aquatic life, nutrient mixing, and the provision of ecosystem services. This result in far-reaching implications for the socioeconomic activities and livelihoods that depend on these water bodies. While some lake associations are taking measures to enhance lakes’ resilience to climate change, a lot more needs to be done. To enhance the climate resilience of African lakes and societies, lake associations are encouraged to implement watershed and water level management, invasive species management practices and enforcement of buffer zones around lakes. There is also a need for community engagement and education on climate-resilient practices, development of ECEs early warning systems and agricultural adaptation if lake dependent communities are to be climate-resilient.Systematic review registrationhttps://www.prisma-statement.org/.